Sex-specific alterations in creatine metabolism in cellular compartments of peripheral blood leukocytes in type 1 diabetes - Nina Alchujyan; Elena Aghajanova; Nina Movsesyan; Arthur Melkonyan; Artashes Guevorkian; Armen Andreasyan; Margarita Hovhannisyan (AIMS Bioengineering)
The creatine (Cr)/creatine kinase (CK) system plays a crucial role in cellular energy metabolism, glucose control, and the immune response. This study aimed to investigate this system in the peripheral blood leukocytes (PBL) of Armenians with type 1 diabetes (T1D) who received insulin therapy. A total of 270 Armenian participants were enrolled in the study and were divided into two age groups: Group I - included children and preadolescents; and Group II - included adolescents and young adults. Within each group, the participants were further categorized based on sex and disease duration: Recent-onset T1D (RO-T1D), and Long-term T1D (LT-T1D). A group of healthy individuals that were matched for age and sex served as controls. The glycemic control (GC) was assessed using the glycated hemoglobin (HbA1c) test. In girls of Group I with LT-T1D, both the Cr levels and CK activity were significantly reduced in both the cytoplasm and mitochondria of the PBL, despite having a good GC. In contrast, age-matched boys showed a relatively stable Cr metabolism. Beginning at puberty, only girls with LT-T1D and a poor GC showed decreased Cr levels and a reduced CK activity, which was most pronounced in the mitochondria. In boys of Group II, the cytoplasmic Cr levels decreased by half, regardless of the GC or disease duration, while the mitochondrial Cr levels decreased by 55% only in boys with LT-T1D and a poor GC. Their CK activity decreased by 80% in both cellular compartments, regardless of the GC and duration of diabetes. Notably, changes in the plasma were less specific. Our findings indicate age- and sex-dependent changes in Cr metabolism in the cytoplasm and mitochondria of PBL in Armenians with T1D, which are influenced by the glycemic status and the disease duration. Further extensive studies in this area may provide insights into potential strategies to control metabolism in T1D to counteract autoimmunity and immune dysregulation, and may also serve as a basis for the development of targeted therapeutic interventions.